ABOUT THE ACTIVITIES OF THE KASHKADARYA REGIONAL BRANCH OF THE WRITERS' UNION OF UZBEKISTAN (E Global Congress, 2024)
This article talks about the establishment of the branch of the Writers' Union of Uzbekistan in the Kashkadarya region and its historical significance. The article mainly reveals the historicity. The development of the region's literary environment and its rapid growth are analyzed.